Genetics and evolution of the Salmonella galactose-initiated set of o antigens. - Peter R Reeves (Public Library of Science (PLoS), 2013)
This paper covers eight Salmonella serogroups, that are defined by O antigens with related structures and gene clusters. They include the serovars that are now most frequently isolated. Serogroups A, B1, B2, C2-C3, D1, D2, D3 and E have O antigens that are distinguished by having galactose as first sugar, and not N-acetyl glucosamine or N-acetyl galactosamine as in the other 38 serogroups, and indeed in most Enterobacteriaceae. The gene clusters for these galactose-initiated appear to have entered S. enterica since its divergence from E. coli, but sequence comparisons show that much of the diversification occurred long before this. We conclude that the gene clusters must have entered S. enterica in a series of parallel events. The individual gene clusters are discussed, followed by analysis of the divergence for those genes shared by two or more gene clusters, and a putative phylogenic tree for the gene clusters is presented. This set of O antigens provides a rare case where it is possible to examine in detail the relationships of a significant number of O antigens. In contrast the more common pattern of O-antigen diversity within a species is for there to be only a few cases of strains having related gene clusters, suggesting that diversity arose through gain of individual O-antigen gene clusters by lateral gene transfer, and under these circumstances the evolution of the diversity is not accessible. This paper on the galactose-initiated set of gene clusters gives new insights into the origins of O-antigen diversity generally.